2006
DOI: 10.1016/j.ccr.2006.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The stress-regulated protein p8 mediates cannabinoid-induced apoptosis of tumor cells

Abstract: One of the most exciting areas of current research in the cannabinoid field is the study of the potential application of these compounds as antitumoral drugs. Here, we describe the signaling pathway that mediates cannabinoid-induced apoptosis of tumor cells. By using a wide array of experimental approaches, we identify the stress-regulated protein p8 (also designated as candidate of metastasis 1) as an essential mediator of cannabinoid antitumoral action and show that p8 upregulation is dependent on de novo-sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
348
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(365 citation statements)
references
References 48 publications
13
348
1
3
Order By: Relevance
“…In line with this observation and with the notion that TRIB3 participates in the regulation of AKT phosphorylation by mTORC2, we found that genetic inactivation of TRIB3 leads to an enhanced phosphorylation of FOXO and BAD but not of GSK3or PRAS 40. Moreover, we recently found that treatment with D 9 -tetrahydrocannabinol (a compound derived from the plant Cannabis sativa that exerts antitumor effects in mouse models of cancer 14,15,35 ) triggers AKT inhibition via an enhanced interaction of TRIB3 with AKT and a subsequent decrease in the interaction of AKT and TRIB3 with the mTORC2 complex. 19 Our data also show that Trib3 interacts more strongly with WT AKT, or with AKT mutants in which Thr 308 and Ser 473 have been mutated to Ala, than with AKT mutants in which these two phosphorylatable residues have been mutated to Asp to mimic the negative charge associated with their phosphorylation (author's unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this observation and with the notion that TRIB3 participates in the regulation of AKT phosphorylation by mTORC2, we found that genetic inactivation of TRIB3 leads to an enhanced phosphorylation of FOXO and BAD but not of GSK3or PRAS 40. Moreover, we recently found that treatment with D 9 -tetrahydrocannabinol (a compound derived from the plant Cannabis sativa that exerts antitumor effects in mouse models of cancer 14,15,35 ) triggers AKT inhibition via an enhanced interaction of TRIB3 with AKT and a subsequent decrease in the interaction of AKT and TRIB3 with the mTORC2 complex. 19 Our data also show that Trib3 interacts more strongly with WT AKT, or with AKT mutants in which Thr 308 and Ser 473 have been mutated to Ala, than with AKT mutants in which these two phosphorylatable residues have been mutated to Asp to mimic the negative charge associated with their phosphorylation (author's unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 In addition, administration of different anticancer agents promotes cancer cell death via TRIB3 upregulation and the subsequent inhibition of Akt. [13][14][15][16][17][18][19] However, the precise molecular basis of the regulation of Akt by TRIB3 and whether loss of this pseudokinase may contribute to cancer initiation and progression remains to be clarified.In this study, we investigated the effect of the genetic inactivation of TRIB3 in several cellular and animal models of cancer. Our findings indicate that genetic inhibition of TRIB3 enhances tumorigenesis and that this effect is due -at least primarily -to a selective inactivation of the transcription factor FOXO by the mammalian target of rapamycin complex 2 (mTORC2)/AKT axis.…”
mentioning
confidence: 99%
“…p8 encodes an 8-kDa nuclear basic helix-loop-helix (bHLH) protein strongly induced in a mouse model of acute pancreatitis and implicated in several diverse functions, including transcriptional regulation, cell cycle control, stress responses, and diabetic renal hypertrophy (2,16,26,30,39,41), as well as apoptotic regulation (2,25).…”
mentioning
confidence: 99%
“…Inhibition of apoptosis correlated with the level of ProTalpha with lowest concentration, demonstrating that the anti-apoptotic was borne by the complex of p8/ProTalpha, the two proteins, being individually inactive. The stress-regulated protein p8 (also deigned as candidate of metastasis 1) was also identified as an essential mediator of cannabinoid antitumoral action and show p8 upregulation is dependent on de novo-synthesized ceramide [18]. It is also observed that p8 mediates its apoptotic effect via upregulation endoplasmic reticulum stress-related genes ATF-4, SHOP, and TRB3.…”
Section: Discussionmentioning
confidence: 99%
“…The FASTA search revealed a partial similarity to the human p8 protein (Table 1). Human p8 protein was over-expressed in many human cancers [11], including breast carcinoma [12] and medullay thyroid [13], and also contributes to the metastatic phenotype [18], although its function has not yet been fully elucidated. Thus, if CLA and other macrolides antibiotics could bind to p8 protein and then interrupt the formation of p8/ProTalpha, it might regulate their apoptotic activity in vivo.…”
Section: Discussionmentioning
confidence: 99%